Transforming Employee Motivation to Enhance Employee Performance at PT Bio Farma (Persero) - Prajnaparamita Leman, Nabila; Gustomo, Aurik (Riviera Publishing, 2023)
This study was conducted at PT Bio Farma (Persero). This Indonesian state-owned company focuses on the research and production of life-science products. During the last three years of implementing the Performance Management System, employee performance has decreased from 2019 – 2021. This study explores the decline in employee performance and the factors that cause it. The research was conducted using quantitative and qualitative analysis methods. The quantitative approach was performed through a survey involving 125 Bio Farma employees as respondents. The survey questions cover 5 (five) elements that can contribute to employee performance: shared values, leadership style, organizational culture, perceptions of organizational practices, and employee motivation. In comparison, the qualitative method was performed through interviews, observation, and internal documentation. To help find root causes and gaps, current practice conditions in the company are also discussed in this study. This study found that employee motivation is the main factor contributing to decreased performance, especially regarding career opportunities and the remuneration system. These business issues lead to proposed solutions to improve the career opportunity system at Bio Farma. Talent management is used in determining the future career of employees. This study suggests the application of competency-based assessment to obtain employee competency data that will be included in employee talent data. The proposed solution will be based on an implementation plan through the implementation of four main activities: identifying employee competencies, defining employee competencies, implementing competency-based assessments, and creating employee talent data which includes performance, potential and competency data.